Drug-induced thrombocytopenia secondary to natalizumab treatment. (30th May 2014) - Cachia, David; Izzy, Saef; Berriosmorales, Idanis; Ionete, Carolina
Summary: A 52-year-old woman with a 10-year history of relapsing-remitting multiple sclerosis (RRMS) was started on natalizumab after she developed side effects for interferon β-1a and glatiramer acetate. The patient presented with acute severe infusion reaction after the third treatment with natalizumab, developing whole-body purpura. Laboratory testing revealed progressive worsening thrombocytopenia up to 3 weeks following natalizumab discontinuation. Platelet antibodies to platelet-specific antigen as well as antibodies against natalizumab were positive. Bone marrow biopsy was negative. The patient was diagnosed with drug-induced immune thrombocytopenia (DITP) as a rare case of natalizumab side effect which was treated with intravenous methylprednisolone followed by rituximab with successful resolution of thrombocytopenia. The patient had a stable course of RRMS with no relapses and no brain MRI changes at 2 years after initiation of rituximab.